A study on the effectiveness in terms of advertisement issue promotion in Yayasan Sabah Market News Scan (MNS) for forest products / Vivie Murhizawatie Murkam - Murkam, Vivie Murhizawatie (2008)
The purposes of this study was to determine whether in term of advertisement issue promotion in magazine Market News Scan for forest product provided by Yayasan Sabah Group is an effectiveness or not and either satisfied to the respondents that include contractors companies and agencies, customer and individuals and also Forestry Division Yayasan Sabah Group itself. At the same time, this study also examines demographic the respondents or customers of magazine Market news Scan, in term of advertisements issue promotion in magazine Market News Scan and an effectiveness of advertisements to attracting customers especially the service and product provided by Forestry Division Yayasan Sabah Group. The result provide an employee profile, the level of choices and preference among the employee include contractors companies and agencies, customer and individuals and also Forestry Division Yayasan Sabah Group itself, employee's opinion and suggestion regarding how to improve in term of advertisement issue promotion in Market News Scan for forest product in Yayasan Sabah Group.